A typology of child abduction events - Erikson, Matt (Legal and criminological psychology, 2002)
Purpose. This study examined the offence of child abduction in England and Wales. Specifically, the relationship of perpetrator to victim and motivation of the perpetrator were considered. It was hypothesized that discrete types of child abduction would be identifiable. Methods. The sample consisted of all offenders convicted of child abduction between 1993 and 1995 identified by the Offenders Index. For each conviction further data were gathered from police records at New Scotland Yard. The resulting sample comprised 149 offenders. These offenders were categorized in terms of relationship to victim and motivation. Results. Four different motivational types of child abduction were identified: sexual, custodial, maternal desire, and ‘other’. The majority of child abductions were sexually motivated, and most child abductions involved female victims. Conclusions. Offence categories are useful for summarizing criminal data but mask factors such as relationship of the perpetrator to the victim, and motivation.